factorise .. x² – 3x² - 9x - 5
Answers
Answered by
1
Answer:
Given that X³ – 3x² – 9x – 5
= x³ + x² – 4x² – 4x – 5x – 5
= x²( x + 1) – 4x ( x + 1) – 5(x + 1)
= (x + 1)(x² – 4x – 5)
= (x + 1)(x² -5x + x – 5)
= (x + 1)(x – 5) (x + 1)
hence, (x +1), (x -5) and (x +1) are the factors of given polynomial .
Similar questions
Social Sciences,
2 months ago
Biology,
2 months ago
Geography,
2 months ago
English,
4 months ago
Sociology,
4 months ago
Math,
11 months ago
Environmental Sciences,
11 months ago